Alumina Supported H3PW12O40 and Ni Catalysts for Hydrocracking of n-Decane - SHENG, JINGYUN; QIU, BO; JIN, HAO; YI, XIAODONG; FANG, WEIPING (Asian Journal of Chemistry, 2010)
A novel series of bifunctional Ni-H3PW12O40/Al2O3 catalysts for the hydrocracking of n-decane were designed and prepared. The evaluation results of these novel catalysts showed that they possessed extremely high catalytic activity for hydrocracking of n-decane and excellent tolerance to the sulfur and nitrogen compounds in the feedstock. In order to reveal the structure and nature of the catalysts, a number of characterizations including XRD, BET, H2-TPD, NH3-TPD and FT-IR of pyridine adsorption were carried out. The characterization results demonstrated that the high catalytic activity and high C5 + selectivity of the catalysts can be attributed to the unique structure of the H3PW12O40 and the interactions between the metal sites and the H3PW12O40.